Computational Atomistic Modeling in Carbon Flatland and Other 2D Nanomaterials - Aurélie Champagne (Applied Sciences, 2020)
As in many countries, the rise of nanosciences in Belgium has been triggered in the eighties in the one hand, by the development of scanning tunneling and atomic force microscopes offering an unprecedented possibility to visualize and manipulate the atoms, and in the other hand, by the synthesis of nano-objects in particular carbon nanostructures such as fullerene and nanotubes. Concomitantly, the increasing calculating power and the emergence of computing facilities together with the development of DFT-based ab initio softwares have brought to nanosciences field powerful simulation tools to analyse and predict properties of nano-objects. Starting with 0D and 1D nanostructures, the floor is now occupied by the 2D materials with graphene being the bow of this 2D ship. In this review article, some specific examples of 2D systems has been chosen to illustrate how not only density functional theory (DFT) but also tight-binding (TB) techniques can be daily used to investigate theoretically the electronic, phononic, magnetic, and transport properties of these atomically thin layered materials.